2006
DOI: 10.1007/s10706-006-6806-7
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of desert sands using municipal solid waste incinerator ash

Abstract: This paper presents experimental results on the use of incinerator ash in stabilizing desert sands for possible use in geotechnical engineering applications. The incinerator ash was added in percentages of 2, 4, 8, 10 and 12%, by dry weight of sand. Laboratory tests such as compaction, unconfined compression, shear box and hydraulic conductivity were performed to measure the engineering characteristics of the stabilized material. The results showed substantial improvements in unconfined compressive strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The results of experiment showed that as the amount of lime and fly ash is increased, there is an apparent reduction in maximum dry density, free swell and swelling capacity under 50 kPa pressure, and a corresponding increase in the percentage of coarse particles, optimum moisture content and CBR value. Mohamedzein et al [13] presented that the engineering properties of the desert sands can be improved significantly by the addition of incinerator ash. Saltan and Findik [19] used the pumice of the Isparta-Karakaya as stabilization material in the subbase layer and showed that pumice can be used as subbase material of highway and the stabilization material when building highway and every kind of road.…”
mentioning
confidence: 99%
“…The results of experiment showed that as the amount of lime and fly ash is increased, there is an apparent reduction in maximum dry density, free swell and swelling capacity under 50 kPa pressure, and a corresponding increase in the percentage of coarse particles, optimum moisture content and CBR value. Mohamedzein et al [13] presented that the engineering properties of the desert sands can be improved significantly by the addition of incinerator ash. Saltan and Findik [19] used the pumice of the Isparta-Karakaya as stabilization material in the subbase layer and showed that pumice can be used as subbase material of highway and the stabilization material when building highway and every kind of road.…”
mentioning
confidence: 99%
“…Recent studies have been directed towards examining the engineering properties of aeolian sands and investigating the ability of using them in construction [6][7][8][9].In the last years, substantial research has been directed to examine different types of additives and their potentiality as stabilizing agents for aeolian sands. Different methods of stabilization have been reported in the literature including the use of cement [10][11][12][13], cement kiln dust [14][15][16][17], bentonite and lime [18][19], bitumen emulsions [20][21],polymer emulsions [22][23][24][25], polypropylene fibers [26][27] and even, waste [28][29][30] Other researchers have accumulated the results of field and laboratory analyses to evaluate dune sands with respect to their use as fine aggregates in cement mortar or concrete, concluding that their use in civil engineering is viable [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Desert sands are usually fine-grained and poorly graded materials with small amounts of silt [1]. Desert sands are not suitable for support of structures and roads, because they are loose and vulnerable to co llapse upon wetting [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for improving the strength of so ils an d o n e o f th e mo st effect iv e meth ods is so il stabilisation. Various methods of soil stabilisation, such as, use of cement [3,4,5,1], cement-by-pass dust [6,7,5], bentonite [8], coal fly ash [9,10,11], asphalt [12], and lime [13], re-enfo rcement of sand by fibres are reported [14,15,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation